Online communities and social computing 4th International Conference, OCSC 2011, Held as Part of HCI International 2011, Orlando, FL, USA, July 9-14, 2011. Proceedings - Ozok, A. Ant; Zaphiris, Panayiotis (Lecture Notes in Computer Science, 2011)
This book constitutes the refereed proceedings of the 4th International Conference on Online Communities and Social Computing, OCSC 2011, held in Orlando, FL, USA in July 2011 in the framework of the 14th International Conference on Human-Computer Interaction, HCII 2011 with 10 other thematically similar conferences. The 77 revised papers presented were carefully reviewed and selected from numerous submissions. The papers accepted for presentation thoroughly cover the thematic area of online communities and social computing, addressing the following major topics: on-line communities and intelligent agents in education and research; blogs, Wikis and Twitters; social computing in business and the enterprise; social computing in everyday life; information management in social computing.